2015
DOI: 10.2991/isci-15.2015.347
|View full text |Cite
|
Sign up to set email alerts
|

Input features of Petroleum Hydrocarbon in Jiaozhou Bay

Abstract: Based on investigation dada on Petroleum Hydrocarbon (PHC) in April, August

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
(6 reference statements)
0
8
0
Order By: Relevance
“…Understanding the source input and storage processes of pollutants is essential to pollution control and environmental remediation in marine bays [3][4]. Jiaozhou Bay is a semi-closed bay located in south of Shandong Peninsula in eastern China, and is surrounded by cities of Jiaozhou, Jiaonan and Qingdao in the north, west and east, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the source input and storage processes of pollutants is essential to pollution control and environmental remediation in marine bays [3][4]. Jiaozhou Bay is a semi-closed bay located in south of Shandong Peninsula in eastern China, and is surrounded by cities of Jiaozhou, Jiaonan and Qingdao in the north, west and east, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Jiaozhou Bay is a semi-closed bay located in south of Shandong Peninsula in eastern China, and is surrounded by cities of Jiaozhou, Jiaonan and Qingdao in the north, west and east, respectively. Previous studies showed that this bay has been polluted by various pollutants including PHC since 1980s [5][6]. This paper analyzed the source input and storage processes of PHC in Jiaozhou Bay using investigation data during 1984-1988.…”
Section: Introductionmentioning
confidence: 99%
“…In nowadays, many marine bays have been polluted by petroleum hydrocarbon (PHC) [1][2][3][4][5][6][7][8][9][10][11]. Understanding the pollution level, source of PHC in marine bay is essential to marine environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…from the aspects of contents, horizontal and vertical distributions, and seasonal distributions [11][12][13][14][15][16][17][18][19][20][21][22][23]. In addition to reveal the environmental conditions of Jiaozhou Bay 1981, the objects of this paper was to provide theoretical basis for pollution prevention and control.…”
Section: Introductionmentioning
confidence: 99%